China's Maritime Security Strategy: An Assessment Of The White Paper On Asia-Pacific Security Cooperation. (2nd January 2017) - Shah, Dhara P.
ABSTRACT: In January 2017, China released its first ever White Paper on Asia-Pacific security cooperation, which sought to embolden Beijing's (littoral) leadership in the region. Highlighting maritime security in the Asia-Pacific as a regional hotspot, the policy paper called for the establishment of a favourable regional order by underlining the merits of cooperative security. Simultaneously, it also sought to entrench China's sovereign interests by displaying a 'reactive assertiveness' in the maritime domain. Referring to the South China Sea (SCS) dispute in particular, the paper declared that while China remained committed to upholding freedom of navigation in the SCS, it would also not shy away from making a "necessary response" to violation of its territorial integrity. Beijing's desire to enhance its economic and military influence in the maritime domain understandably has an effect on the security calculus of the Asia-Pacific. In response to China's growing military capabilities and assertiveness in international waters, other regional players have also been emboldened or forced to stake territorial claims in the interest of their sovereignty. The consequent insecurity, tension and power play is likely to have a destabilising effect on the region. It is in this context that this paper attempts to analyse China's maritime security strategy as outlined in the White Paper, on three counts: by analysing threat perceptions from the Chinese perspective, by outlining the need to build a comprehensive maritime security framework that addresses the interests of all stakeholders in the region and, finally, by analysing security implications for India.